2023
DOI: 10.21037/atm-22-6515
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption in multiple health outcomes: an umbrella review of meta-analyses of observational and clinical studies

Abstract: Background: Omega-3 polyunsaturated fatty acids are known to be associated with numbers of health benefits, and which can be uptake from fish. The aim of this study was to evaluate the current evidence of associations between consumption of fish and diverse health outcomes. Here, we performed an umbrella review to summarize the breadth, strength, and validity of the evidence derived from meta-analyses and systematic reviews of fish consumption on all health outcomes. Methods:The methodological quality of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…According to our analysis, we can estimate that high vs. low intake of fish would reduce CVD risk by a factor of up to 10%. This general result is broadly confirmed by the results from previous systematic reviews and meta-analyses [6,9,10,41,42]. Nevertheless, a reduced CVD risk in relation to fish intake was observed in the large majority of the included studies with two studies reporting a null association between fish intake and CVD risk [27,37] and two studies reporting an increased CVD risk for high intake of fish [35,39].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…According to our analysis, we can estimate that high vs. low intake of fish would reduce CVD risk by a factor of up to 10%. This general result is broadly confirmed by the results from previous systematic reviews and meta-analyses [6,9,10,41,42]. Nevertheless, a reduced CVD risk in relation to fish intake was observed in the large majority of the included studies with two studies reporting a null association between fish intake and CVD risk [27,37] and two studies reporting an increased CVD risk for high intake of fish [35,39].…”
Section: Discussionsupporting
confidence: 82%
“…Epidemiological studies have consistently shown that eating a moderate balanced diet containing potentially healthy foods such as fish can significantly help reduce CVD incidence and mortality [4]. For example, fatty fish such as sardine, salmon, trout and mackerel contain high amounts of long-chain omega-3 polyunsaturated fatty acids (ω-3 PUFA), namely docosahexaenoic acid (DHA; 22:6n-3) and eicosapentaenoic acid (EPA; 20:5n-3), which may reduce the risk of CVD [5][6][7]. Additionally, prospective studies have reported an association between fish consumption and CVD events [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, in the present study, fish intake did not turn out to be associated with the participants’ body mass index. Even though one might believe that due to the numerous health benefits of eating fish [ 6 , 7 , 8 , 9 ], higher fish intake might be connected to having a proper body mass index, the results from the European Prospective Investigation into Cancer and Nutrition (EPIC) showed neither a relation between higher fish intake and lower body mass [ 79 ], nor between higher fish intake and waist circumference [ 80 ]. In the present study, another explanation of no differences might also simply be the fact that fish intake is in general very low among secondary school students.…”
Section: Discussionmentioning
confidence: 99%
“…Fish consumption is associated with several significant health benefits. In an umbrella review of meta-analyses, it was found that high fish intake was associated with various beneficial health outcomes, including decreased all-cause death rate, decreased risk of different types of cancers (including colorectal, lung, hepatocellular, and oral cancer), and reduced risk of some cardiovascular diseases, such as the acute coronary Nutrients 2024, 16, 853 2 of 22 syndrome, heart failure, and stroke [7]. Another one showed that fish consumption was also associated with a reduced risk of depression [8].…”
Section: Introductionmentioning
confidence: 99%
“…Meats make up a significant part of the diet and have been linked to some malignancies, including GI cancers [4][5][6]. So far, several systematic reviews and meta-analyses have examined the relationship between meat and meat product consumption and GI cancers [4,5,[7][8][9][10][11][12][13][14][15]. While several valuable systematic reviews and meta-analyses have investigated the association between meat consumption and GI cancers, these studies have primarily focused on the effect on individual cancers (e.g., colorectal cancer) and lacked a comprehensive analysis across all major GI cancers (stomach, esophagus, etc.).…”
Section: Introductionmentioning
confidence: 99%